Faktor-Faktor yang Berhubungan dengan Pelaksanaan Inisiasi Menyusui Dini - Heryanto, Eko (Universitas Aisyah Pringsewu, 2016)
Early neonatal death occurred on the first day. Breast-feeding (breast milk) and feeding the first hour of life, known as Early Initiation of Breast-feeding (IMD) and followed by 6 months of exclusive breastfeeding can prevent infant mortality. At the hospital Dr. H. Ibnu Sutowo, number birth January-March 2014 as many as 418 deliveries, and of that number only 13.39% (56 deliveries) that perform IMD while the rest do not. The purpose of this study was to determine the factors associated with the implementation of the IMD In Maternity Room Hospital Dr. H. Ibnu Sutowo Baturaja. Method this research was conducted with cross-sectional design, data collection research done by structured interviews using questionnaires. The population in this study were all mothers delivered with normal birth process in Maternity Space Room Hospital Dr. H. Ibnu Sutowo Baturaja in May 2014.The results ofthis study are known from as much as 25.3% of respondents 83 to implementthe IMD, 51.8% withgood knowledge, 59% with a positive attitude, 60.2% have nofamily support, and 61.4% received support from health workers. Results bivariate analysis showed a variable correlation of knowledge, attitude, family support and support of health workers with p value 0.005 respectively; 0.002; 0.008 and 0.017.Conclusion of all the variables in this study no significant association.Keywords: IMD, Infant Mortality